2014
DOI: 10.1007/s11239-014-1123-0
|View full text |Cite
|
Sign up to set email alerts
|

Over-testing for heparin induced thrombocytopenia in hospitalized patients

Abstract: Heparin induced thrombocytopenia (HIT) is a pro-thrombotic and potentially fatal complication of heparin therapy. Its diagnosis rests on high clinical probability and the laboratory demonstration of anti-PF4/heparin antibodies. The high prevalence of thrombocytopenia in hospitalized patients and the high sensitivity but low specificity of immunoassays for HIT antibodies can lead to over-testing and over-diagnosis. We conducted a study to review HIT screening practices in a tertiary care setting. We reviewed 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
(29 reference statements)
0
21
0
Order By: Relevance
“…Moreover, Alpert et al found the prevalence of heparin/PF4 antibodies ranging between 4 and 15% in patients with antiphospholipid syndrome and systemic lupus erythematosus, respectively, often in the absence of clinical HIT or recent heparin exposure ( 23 ). As previous cases demonstrate, leaning on positive immunoassay alone can lead to a wrong suspicion about HIT and potential use of other anticoagulant drugs that can cause bleeding and additional healthcare costs ( 24 - 26 ). For that and similar reasons samples positive for HIT-autoantibodies in immunoassays should be evaluated by the functional tests.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Alpert et al found the prevalence of heparin/PF4 antibodies ranging between 4 and 15% in patients with antiphospholipid syndrome and systemic lupus erythematosus, respectively, often in the absence of clinical HIT or recent heparin exposure ( 23 ). As previous cases demonstrate, leaning on positive immunoassay alone can lead to a wrong suspicion about HIT and potential use of other anticoagulant drugs that can cause bleeding and additional healthcare costs ( 24 - 26 ). For that and similar reasons samples positive for HIT-autoantibodies in immunoassays should be evaluated by the functional tests.…”
Section: Discussionmentioning
confidence: 99%
“…4 The 4T score has been validated in numerous adult studies and a low 4T score (1 to 3) has a 99.8% negative predictive value. Given the ready availability of high-sensitivity, low-specificity H-PF4 antibody assays, it is not surprising that HIT is commonly suspected and tested for.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin-induced thrombocytopenia (HIT) is an immune-mediated prothrombotic disease in response to previous heparin exposure [1] Direct thrombin inhibitors (DTIs) are suitable candidates for the prophylaxis of thrombosis in patients with HIT [2][3][4][5][6]. Bivalirudin, a common DTI, can be considered as a therapeutic alternative to heparin [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%